Psychological relationship of students' logic and reasoning skills in the context of critical thinking - Molbassynova, Zhumakul; Gelişli, Yücel; Murzagulova, Meiramkul; Zhamirova, Ulmeken; Danikeeva, Aigul (Habaršy. Psihologiâ ža̋ne sociologiâ seriâsy (Online), 2024)
In the article, one of today's actual issues is in the direction of supporting new ideas proposed by young intellectuals In the context of critical thinking, the theoretical and methodological bases of the psychological relationship between students' logic and reasoning skills were studied. In this direction, the concepts of "thinking", "critical thinking", "logic", "reasoning skills", "psychological relations of students' logic and reasoning skills on the basis of critical thinking " were defined , which allow for theoretical justification through a review of philosophical, psychological and pedagogical scientific literature. In the course of the research, based on synergistic, motivational, and cognitive methodological foundations, the psychological relationship of students' logic and reasoning skills in the context of critical thinking structure done and An integrated diagram of the concepts related to the individual's critical thinking, understanding, modification, verification, determination and preparation of evidence, logical decisions and conclusions, cognitive skills and reasoning skills, mindset and communication was depicted. As a result of the practical-experimental results organized in the direction of defining the theoretical-methodological bases studied by the authors in the article, in the context of critical thinking, through the function of the psychological relationship between the logic and reasoning skills of students, their thinking logic and reasoning skills have increased and their desire to obtain a successful education has increased, and in the process of entering into communication It was shown that he can express his own thoughts, provide evidence, analyze it, make optimal decisions, and get directions for regulating his activity and behavior.